2021
DOI: 10.3390/ijerph18041518
|View full text |Cite
|
Sign up to set email alerts
|

Climate Action at Public Health Schools in the European Region

Abstract: Climate change is putting the achievement of all Sustainable Development Goals at risk and leads to negative impacts on human health and well-being. Consequently, tremendous social responsibility lies with public health professionals and their associations. Therefore, this study addressed the following question: “How can the Association of Schools of Public Health in the European Region (ASPHER) best support the goals of the European Green Deal through its network of public health schools and departments?” Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…There has been little coordination among institutions of higher learning and development of programs to address this need ( 4 ). Only recently, formalized curriculum and programs have been established, particularly in schools and programs of public health ( 5 7 ). Many of the significant advancements in medical school education around the topic of climate and health have been advocated and requested by medical students ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been little coordination among institutions of higher learning and development of programs to address this need ( 4 ). Only recently, formalized curriculum and programs have been established, particularly in schools and programs of public health ( 5 7 ). Many of the significant advancements in medical school education around the topic of climate and health have been advocated and requested by medical students ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both our conclusions and numerous previous studies have demonstrated a different level of awareness of climate change according to students’ sex and educational level, which would imply the design of different strategies according to these parameters, which should be included in the different curricula so that future generations have better knowledge and awareness and a sufficiently proactive attitude to generate a substantial transformation in the struggle against climate change. These strategies should be developed using a systemic approach (Orhan et al, 2021), planning combined learning (E. H. Lee, 2016) and in-situ knowledge (Delgado et al, 2021), and they should run parallel to greater teacher training in awareness of climate change, accompanied by the pedagogical means and resources needed to actively convey this type of knowledge. To address this problem in a global fashion, a review of the textbooks used is also needed to both ensure their scientific rigour and to update them, adapting them to innovative, creative activities that foster student motivation (Seguido & Cantos, 2021) and enlarging the scope of the contents on this theme to as many school subjects as possible (Onuoha et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Tanto nuestras conclusiones como numerosos estudios previos han demostrado un nivel de conciencia diferente frente al cambio climático en función del sexo y nivel escolar de los estudiantes, lo que implicaría el diseño de estrategias diferenciadas en función de estos parámetros que se deberían incluir en los distintos planes de estudios con el fin de que las generaciones futuras dispongan de un mayor conocimiento, sensibilización y actitud pro-activa suficiente para generar una transformación sustancial en la lucha contra el cambio climático. Estas estrategias deben configurarse bajo un enfoque sistémico (Orhan et al, 2021), planteando el aprendizaje combinado (E. H. Lee, 2016) y el conocimiento in situ (Delgado et al, 2021), e ir en paralelo a una mayor formación de los docentes en la concienciación sobre el cambio climático, acompañado de los medios pedagógicos y recursos necesarios para transmitir este tipo de conocimiento de una forma activa. Para abordar esta problemática de forma global, se requeriría también una revisión de los libros de texto empleados, tanto para asegurar su rigor científico como para actualizarlos, adaptándolos a propuestas de actividades innovadoras y creativas que fomenten la motivación del estudiante (Seguido y Cantos, 2021), y ampliando el alcance de los contenidos sobre esta temática al mayor número de materias escolares posibles (Onuoha et al, 2021).…”
Section: Discusión Y Conclusionesunclassified
“…In Europe, the Agency for Public Health Education Accreditation (APHEA) was established as a criterion for accreditation of educational programs: the demonstration of “ appropriate responsiveness to emerging scientific evidence and developments in the public health academic and professional spheres and to changes in the environment and health needs and demands of populations ” [13]. The Association of Schools of Public Health in the European Region (ASPHER) developed a survey on the implementation of climate and health education in European public health schools, where it was demonstrated that climate and health education were unable to meet the actual needs of the public health field [14]. Following this survey and considering the importance of promoting the inclusion of climate change-related topics in the education and training of health professionals, ASPHER published a set of competencies for public health professionals in Europe, considering four domains: knowledge and analytical skills, communication and advocacy, collaboration and partnerships, and policy [15] (Fig.…”
Section: Assessment Of the Training Needsmentioning
confidence: 99%